Power converters for grid integration of solar energy - Ang, Ying Ying (2010)
In the present society, the focus is on both adequacy of energy supply long-term and also the environmental implication. Solar energy can obtain from using the photovoltaic (PV) and the energy obtain is a clean and abundant source of energy that can produce electricity without any emission of pollutant gases or noises. But as the PV systems nowadays still have relatively low conversion efficiency so it is essential to develop an efficient control technique which would harvest the maximum available PV power. The purpose of this report is to document the developed control technique and inverter topology that has been implemented in this project. Studies on PWM techniques, types of inverter and MPPT algorithm will be discuss. Subsequently, we will be discussing on the use of MATLAB and dSPACE in this project. Lastly, experimental results of the hardware prototype will be discussed when using different values of modulation index and shoot through duty ratio.